Prenatal diagnosis of Duchenne muscular dystrophy in 131 Chinese families with dystrophinopathy. (6th March 2017) - Wang, Huanhuan; Xu, Yan; Liu, Xiaoqing; Wang, Lei; Jiang, Wenting; Xiao, Bing; Wei, Wei; Chen, Yingwei; Ye, Weiping; Ji, Xing
Abstract: Objectives: The objective of this study is to report 6‐year clinical prenatal diagnosis experience of Duchenne muscular dystrophy (DMD)‐affected families evaluated at a single prenatal diagnosis center in China and establish a reliable and rational prenatal diagnosis procedure for DMD families. Methods: The prenatal diagnosis data of 146 at‐risk pregnancies in 131 DMD families referred to our center from 2010 to 2016 were retrospectively reviewed. Results: The mutation detection rate of the probands was greater than 99%. In the 131 families, 50 mothers showed negative results during carrier testing, and de novo exon deletions arose in 51.1% of the probands. Of the 146 pregnancies, 91 were male fetuses, 34 of which were affected. Germline mosaicism was identified three times in this cohort, and recombination of the DMD gene was detected in nine cases. Conclusions: Accurate genetic diagnosis of the proband is important for preventing recurrence in at‐risk families. The present results demonstrate the importance of considering maternal germline mosaicism in the genetic assessment. Prenatal diagnosis should be suggested to the parent with a DMD proband whether carrier testing found the causative mutation in the mother's blood or not. Finally, we have developed a prenatal diagnosis algorithm for dystrophinopathies that combines multiplex ligation‐dependent probe amplification, quantitative PCR, sequencing and linkage analyses. © 2017 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Prenatal diagnosis is important for families with DMD recurrence risk. The mutant spectrum of DMD is wide, and different methods are used to detect the various types of mutations. Germinal mosaicism, de nov o mutations and recombination events have a relatively high frequency in the transmission of DMD. What does this study add? Accurate genetic diagnosis of the proband is important to prevent recurrence in the prenatal diagnosis, and the mutation detection rate of the probands was greater than 99% in our research. Considering the relatively high frequency of germinal mosaicism, prenatal diagnosis should be suggested to the parent with a DMD proband whether carrier testing found the causative mutation in the mother's blood or not. Different methods including MLPA, quantitative PCR, sequencing and STR linkage analyses should be combined in DMD prenatal diagnosis for a more reasonable procedure and more accurate diagnostic results.